MAKNA MOTIF TENUN IKAT DASAR BAGI PEMUDA (STUDI FENOMENOLOGI PADA SUKU UMA BADUT DI DESA MAKTIHAN KECAMATAN MALAKA BARAT KABUPATEN MALAKA) - Seran, Lenisiati; Selly, Frans Kristian; Mardani, Ambara Saraswati (Education For All, 2024)
The purpose of this study was to determine the meaning of the ikat weaving motif for the youth of the Uma Badut tribe. This research method uses a qualitative method with a phenomenological study approach. The research location is the Uma Badut tribe in Maktihan village, West Malaka District, Malaka Regency. The subjects in this study were the Uma Badut tribe community consisting of youth, weaving mothers and traditional elders. Data analysis techniques include data collection, data reduction, data presentation and conclusion drawing. Research Results One of the woven motifs that is still relevant to the life of the Uma Badut tribe is the uma nen motif. The uma nen motif has a deep meaning and value contained in it. In the lives of the youth of the Uma Badut tribe, from generation to generation they have preserved these two values. However, today's youth do not understand these two values, due to a lack of teaching from parents or traditional elders. Therefore, based on these results it can be concluded that the Uma Badut tribe has basic motifs that have deep meaning and value contained in woven fabrics. However, many young people from the Uma Badut tribe do not live up to the values conveyed by their ancestors. Keywords: Meaning, Motif, Ikat Weaving, Youth